An Analysis of Javanese Registers in Traditional Markets - Cahya, Adellya Dwi; Aristiani, Dianita; Astuti, Indah Diah (Universitas Teknokrat Indonesia, 2025)
This article discusses the exploration of Javanese language variation used in the context of traditional markets in Magelang City, Central Java, which focuses on register. The definition of the register itself is one of the linguistic phenomena where a word can have different meanings depending on the context or in a particular field. We conducted this research in one of the traditional markets in Magelang City, Central Java. This research was prepared using qualitative research with data collection methods of participatory observation and data analysis in the form of audio recordings containing interactions between sellers and buyers. In this case, this research used descriptive data analysis techniques to understand Javanese language variation and identify specific registers and contextual meaning in the context of traditional markets. From the result of the analysis, some specific registers were found, such as